Complication Severity and Its Association with the Treatment Management of COVID-19 Patients in Bangladesh: A Cross-Sectional Study - Hossain, Syed Billal; BakiBillah, Abul Hasan; Ali Haidari , Basit; Chowdhury, ABM Alauddin (Health Nexus, 2023)
In an unprecedented way, COVID-19 patients in Bangladesh have suffered greatly due to the severity of the complications. Additionally, treatment management was also a grave concerning issue. This study explored the extent of COVID-19 complications associated with the pattern of COVID-19 Prevention and Treatment Management in the context of Bangladesh. This cross-sectional study included 659 COVID-19-positive patients aged 18 and up who were treated at home or in hospitals and lived in Dhaka city From April to September 2021. The results showed that 20.5% had a mild COVID-19 infection. Family income, the number of co-morbidities, and the location of therapy were found to have a substantial impact on recovery time. In addition, there were high correlations between age, the number of co-morbidities, level of education, and the place of treatment with the severity of Covid-19 infection. The government should place a greater emphasis on training and resources to ensure efficient hospital management and widespread public knowledge as a precaution for further phenomena like COVID-19.